Gap Junctions between Endothelial Cells Are Disrupted by Circulating Extracellular Vesicles from Sickle Cell Patients with Acute Chest Syndrome - Gemel, Joanna; Mao, Yifan; Lapping-Carr, Gabrielle; Beyer, Eric C. (International journal of molecular sciences, 2020)
Intercellular junctions maintain the integrity of the endothelium. We previously found that the adherens and tight junctions between endothelial cells are disrupted by plasma extracellular vesicles from patients with sickle cell disease (especially those with Acute Chest Syndrome). In the current study, we evaluated the effects of these vesicles on endothelial gap junctions. The vesicles from sickle cell patients (isolated during episodes of Acute Chest Syndrome) disrupted gap junction structures earlier and more severely than the other classes of intercellular junctions (as detected by immunofluorescence). These vesicles were much more potent than those isolated at baseline from the same subject. The treatment of endothelial cells with these vesicles led to reduced levels of connexin43 mRNA and protein. These vesicles severely reduced intercellular communication (transfer of microinjected Neurobiotin). Our data suggest a hierarchy of progressive disruption of different intercellular connections between endothelial cells by circulating extracellular vesicles that may contribute to the pathophysiology of the endothelial disturbances in sickle cell disease.